The impact of nosocomial postoperative wound infection on the cost of hospitalization in Obstetric and Gynecologic Unit, Sleman General Hospital,1992/1993 - Stephani M, Stephani M (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1997)
Nosocomial postoperative wound infection is a combined clinical and managerial problem. This report discusses the impact of nosocomial postoperative wound infection on the cost of hospitalization, in the Obstetric and Gynecologic unit, Sleman General Hospital in 1992/1993. There are two methods of nosocomial postoperative wound infection examination used in this study, namely: (1) comparative analysis among infected with uninfected and (2) subjective comparison study. The result of the first method showed a total cost increase of Rp. 74,877.00 and subjective comparison yielded total cost increase of Rp. 3,112,371.80. Based on the diagnosis, the additional cost of nosocomial infection is as follows: (1) for Cephalopelvic Disproportion; Rp. 224,081.61; (2) for twin pregnancy, premature rupture of membranes, and prolonged pregnancy; Rp 290,457.09; (3) for uterine myoma (30 hospital days), the additional cost of nosocomial infection is Rp 513,564.66; (4) for premature rupture of membrane, and fetal distress, Rp. 75,793.87; (5) for malignant neoplasm of ovary; Rp. 328,838.70; (6) for malignant neoplasm of uterine cervix, Rp. 374,326.44; (7) for premature rupture of membranes, prolonged first stage and failure of vacuum extraction, the additional cost of nosocomial infection is Rp. 251,563.22; (8) for premature rupture of membranes, failure of induction of labor by medical methods and fetal distress, Rp. 177,619.35; (9) for uterine myoma (12 hospital days), 876,126.86. It is recommended, therefore, that nosocomial infection control committee should be established in Sleman General Hospital. The Committee will assist the hospital director in planning, implementing, monitoring and evaluating nosocomial infection control activities. A social marketing program to improve aseptic techniques, the use of appropriate antiseptic and the maintenance of sterility in the operating room should be implemented so that nosocomial infection can be prevented and may reduce the cost of hospital care.Key words: nosocomial infection - post operative wound infection - cost of treatment - comparative analysis - subjective comparison